Healthcare as a Universal Human Right Sustainability in Global Health - Nunes, Rui (Taylor & Francis, 2021)
This important book outlines how, despite varying levels of global socio-economic development, governments around the world can guarantee their citizens' fundamental right to basic healthcare. Ground in the philosophical position that healthcare is an essential element to human dignity, the book moves beyond this theoretical principle to offer policy makers a basis for health policies based on public accountability and social responsiveness. Also emphasizing the importance of global co-operation, particularly in the area of health promotion and communication, it addresses, too, the issue of financial sustainability, suggesting robust mechanisms of economic and social regulation. New opportunities created by e-health, evidence-based data and artificial intelligence are all highlighted and discussed, as is the issue of patient rights. Students and researchers across bioethics, public health and medical sociology will find this book fascinating reading, as will policy makers in the field.